BOSHLANG‘ICH SINF ZAMONAVIY ONA TILI DARSLARIDA LEKSIK TUSHUNCHALAR HAQIDA TASAVVUR HOSIL QILISH METODLARI (Conferencea, 2022)
This article discusses methods of creating lexical concepts in elementary school modern mother tongue lessons, the history of the study of the lexical concept system, and the sources of enrichment and program requirements for teaching lexical concepts in primary education.